2006
DOI: 10.3998/ark.5550190.0007.908
|View full text |Cite
|
Sign up to set email alerts
|

Chromones and bischromones: an account of photoinduced reactions

Abstract: This account provides a survey of phototransformations of chromones occurring through the cycloadditions, oxidations, isomerizations and reorganizations. Photochemistry of the variety of bischromones occurring through intramolecular photo-H-abstractions and thus leading to angular tetracyclic photoproducts has also been reviewed. In the bischromones, the photoproduct formations and their distributions were found to be dependent upon the length and structure of the intermediate spacer units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Tetrahydrobenzo[b]pyran-based compounds possess the potential for physical enhancers in treating neurological diseases such as Alzheimer's and Parkinson's diseases, Dawson's syndrome, amyotrophic lateral sclerosis, Huntington, Schizophrenia, AIDS-associated dementia, and myoclonus [ 7 ]. Also, these compounds are widely used in cosmetics and as pigments [ 8 ].
Scheme 2 Pyran-based natural and synthetic drugs in clinical use [ 3 ].
…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahydrobenzo[b]pyran-based compounds possess the potential for physical enhancers in treating neurological diseases such as Alzheimer's and Parkinson's diseases, Dawson's syndrome, amyotrophic lateral sclerosis, Huntington, Schizophrenia, AIDS-associated dementia, and myoclonus [ 7 ]. Also, these compounds are widely used in cosmetics and as pigments [ 8 ].
Scheme 2 Pyran-based natural and synthetic drugs in clinical use [ 3 ].
…”
Section: Introductionmentioning
confidence: 99%
“…Chromones are widely present in nature, especially in the plant kingdom, and a wide variety of useful biological properties are associated with them [ 1 2 ]. Chromone derivatives act as effective tyrosine and protein kinase C inhibitors [ 3 ] and display antifungal [ 4 – 5 ], antimycobacterial [ 6 ], antiviral [ 7 ], antihypertensive [ 8 ], anti-oxidant [ 9 12 ], HIV-inhibitory [ 13 ], anti-inflammatory [ 14 – 15 ], immunomodulatory [ 16 ], antithrombotic [ 17 ], and anticancer [ 18 20 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, Panda et al reported the synthesis of 3,4-dihydro-2 H -1,4 oxazines via Ag( i ) promoted intramolecular cyclization. 6 During the exploration of platinum catalysed domino cycloisomerization–hydroalkoxylation reactions of alkyne-diol derivatives for the synthesis of fused bicyclic acetals, the Ley group highlighted the potential regioselectivity problems in such transformations (Scheme 1, eqn (2)). 7 Similar potential regioselectivity issues were observed independently by Van der Eycken (for morpholine vs. oxazepine) and Schreiber (for oxazepanone vs. oxazocenones).…”
mentioning
confidence: 99%